Bioremediation kinetics of pyrene by microbial consortium isolated from local polluted soil - Ibn Abubakar, Baba Shehu Umar (2014)
Pyrene (Pyr), a toxic four-ring polycyclic aromatic hydrocarbon (PAHs) pollutant, is often found at a relatively high concentration in soil sediments of polluted sites. It has been used as a model substrate for higher molecular weight PAHs bioremediation studies. In spite of abundant works on isolation, characterization and application of PAHs degrader, information on bioremediation kinetics and optimisation of Pyr remediation is still very rare. Consequently, the present research aims at isolation and identification of major consortia of Pyr-degrading bacteria from a local polluted site; develops biodegradation kinetics under different operating parameters and investigate their remediation capability using different Pyr-spiked soils. A mixed culture was isolated from a hydrocarbon-contaminated soil by enriching with 1.5 ppm of Pyr as sole source of carbon and energy. The phenotype of mixed culture was identified by screening and biochemical methods. Inoculum was grown in nutrient broth supplemented with 0.75 ppm of Pyr for aqueous degradation, and with 100 ppm of Pyr in a mineral salt medium supplemented with 1% of yeast extract for the development of kinetics. Investigation was conducted on the degradation of Pyr in aqueous medium using different range of Pyr concentrations (10 ppm-100 ppm and 100 ppm-700 ppm) as carbon source and monitored over the period of 15 days. The progress of pyrene degradation was quantitatively monitored using HPLC. Surface response methodology was employed as a design tool in optimizing bioremediation of Pyr-spiked soils with various sets of operating conditions in a soil-slurry batch reactor. The initial screening from the mixed-culture showed 14 types of microbial strains isolated: 12 strains were identified biochemically as Bacillus cereus and the remaining 2 were identified as Enterobacter aerogenes. Degradation of 1.5 ppm and 3.0 ppm of Pyr and biomass growth in aqueous medium occurred within six days with a short lag period followed by log phase from day 2- day 6 with moderate specific growth rate, _ at 0.07 h 1 and 0.024 h 1 respectively. For both cultures, more than 90 % of Pyr was degraded during this log phase growth period and thus can be classified as"growth associated" degradation kinetics. Investigation on environmental factors showed that they grew well at mild acidic to neutral pH of 4 to 7 and did not grow at pH 8. In addition, the effect of temperature indicated that the culture grows favourably at a range of temperature of 20oC and 30oC and not with temperature of 40oC. Moreover, preliminary investigate from the culture media using GCMS revealed the metabolites of naphthalene, benzenepropanl, 1,4-benzenediol, benzoic acid, ethanone, 2(3H0)-Furanone, 1,2-benzenedicarboxylic acid, dibutyl phthalate and Di-n-octyl phthalate. From the results of the soil-slurry batch reactor,biomass growth was dependent on Pyr concentration and slurry's initial pH,but not soil/water ratio. A ratio of Pyr to soil of 1000 mg/kg and the initial pH of 5 resulted in the highest percentage of Pyr removal. There is linear relationship between initial pH and nal pH, while the soil/water has no effect on the growth of the biomass in the reactor. Probably due to the chosen range of soil/water ratio of (0.1-0.2) might provide adequate space for mixing and microbial mobility within the soil-slurry reactor. Initial screening of concentration shows that, the mixed culture could not grow above concentration range of (100 ppm-700 ppm). Subsequently, the concentration ranges of between (100 ppm-700 ppm) and (10 ppm-100 ppm) were used for the development of the kinetics. The result of degradation kinetics developed were fitted into Monod equation, with r2 0.67, and r2 0.68, respectively. However, degradation models of Haldane, Webb, Yano and Aiba could not describe the degradation kinetics of the mixed culture. Consequently,there is non-conformity of the mixed culture to Monod model, although the correlation. coeficient shows 67% and 68%, and fairly described by the Monod model,which describes microbial growth with respect to substrate depletion. Therefore,and probably, the mixed culture growth differently within the culture medium or perhaps their synergy on the growth substrate depends on different metabolites within the culture medium.